Cortical color blindness is not "blindsight for color". - Heywood, C; Kentridge, R; Cowey, A (1998)
Cortical color blindness, or cerebral achromatopsia, has been likened by some authors to "blindsight" for color or an instance of "covert" processing of color. Recently, it has been shown that, although such patients are unable to identify or discriminate hue differences, they nevertheless show a striking ability to process wavelength differences, which can result in preserved sensitivity to chromatic contrast and motion in equiluminant displays. Moreover, visually evoked cortical potentials can still be elicited in response to chromatic stimuli. We suggest that these demonstrations reveal intact residual processes rather than the operation of covert processes, where proficient performance is accompanied by a denial of phenomenal awareness. We sought evidence for such covert processes by conducting appropriate tests on achromatopsic subject M.S. An "indirect" test entailing measurement of reaction times for letter identification failed to reveal covert color processes. In contrast, in a forced choice oddity task for color, M.S. was unable to verbally indicate the position of the different color, but was surprisingly adept at making an appropriate eye movement to its location. This "direct" test thus revealed the possible covert use of chromatic differences.